Ethnoscience-Based Digital Learning Media in Science Learning for Junior High School Students: A Systematic Review of the Literature - Dewi Khoirun Nisa; Fikri Natadiwijaya; Asri Widowati (Pusdikra Publishing, 2026)
Ethnoscience-based digital learning media in science learning is an innovation that integrates science with local culture. This study aims to identify what digital media are used to integrate ethnoscience, relevant science topics, impact on aspects of learning outcomes, and challenges in implementing ethnoscience-based digital media through a systematic literature review using the PRISMA guide. Of the 271 articles identified, 13 articles were selected based on inclusion and exclusion criteria. The results of the study show that ethnoscience-based digital media is effective in improving concept understanding, science literacy, science process skills, motivation, environmental literacy and cultural literacy. The integration of local culture in digital media helps students connect science concepts with everyday life, thus creating more relevant and meaningful learning. However, challenges such as limited technological infrastructure, teacher readiness, and student adaptation to digital learning are still major obstacles. Collaboration between educators, educational institutions, and governments is needed to overcome these constraints, by providing adequate training and resources.